Integrating Nyadran Tirta Wening Cultural Values into IPAS Learning to Develop Elementary Students’ Ecological Intelligence - Ella Rahma Nura Aziza; Ari Metalin Ika Puspita; Nadi Suprapto (ATTA`DIB, 2025)
Abstract This study aims to analyze the integration of Nyadran Tirta Wening cultural values into IPAS (Integrated Natural and Social Science) learning to develop elementary students’ ecological intelligence. A qualitative approach with a case study design was employed at SD Negeri 2 Jati from October 2025. The participants included a classroom teacher, third-grade students, the principal, and community members involved in the Nyadran Tirta Wening tradition. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The results indicate that cultural values such as gratitude for water sources, cooperation, and environmental care were successfully integrated into IPAS learning through school-based project activities. This process fostered students’ ecological awareness, understanding, and responsible actions toward nature. The combination of local wisdom and scientific learning created meaningful, contextualized learning experiences that enhanced students’ moral and environmental sensitivity. The study concludes that integrating local cultural values into IPAS learning is an effective pedagogical strategy to promote ecological intelligence while preserving Indonesia’s cultural heritage. Keywords: Nyadran Tirta Wening, IPAS, local wisdom, ecological intelligence, school-based project Abstrak Penelitian ini bertujuan untuk menganalisis integrasi nilai-nilai budaya Nyadran Tirta Wening dalam pembelajaran IPAS guna mengembangkan kecerdasan ekologis siswa sekolah dasar. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus yang dilaksanakan di SD Negeri 2 Jati pada bulan Oktober 2025. Subjek penelitian meliputi guru kelas, siswa kelas III, kepala sekolah, dan tokoh masyarakat yang terlibat dalam tradisi Nyadran Tirta Wening. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa nilai-nilai budaya Nyadran Tirta Wening seperti rasa syukur terhadap sumber air, gotong royong, dan kepedulian lingkungan berhasil diintegrasikan dalam pembelajaran IPAS melalui kegiatan proyek berbasis sekolah. Proses ini mampu menumbuhkan kesadaran, pemahaman, dan tindakan ekologis pada siswa. Pembelajaran yang menggabungkan kearifan lokal dengan sains menciptakan pengalaman belajar yang bermakna dan relevan dengan kehidupan siswa. Penelitian ini menyimpulkan bahwa pengintegrasian nilai budaya lokal ke dalam pembelajaran IPAS merupakan strategi efektif untuk mengembangkan kecerdasan ekologis sekaligus melestarikan kearifan budaya bangsa. Kata kunci: Nyadran Tirta Wening, IPAS, kearifan lokal, kecerdasan ekologis, proyek sekolah.